THEORETICAL STUDY OF THE [Fe(en)2(NCS)2] COMPLEX WITH REPARAMETERIZED DENSITY FUNCTIONALS - Yusthinus T. Male; Djulia Onggo; Muhamad A. Martoprawiro; Ismunandar Ismunandar (Universitas Gadjah Mada, 2009)
Quantum chemical studies have been carried out on the Fe(en)2(NCS)2 (en = ethylenediamine) complex both in low and high spin states (S = 0 and S = 2) using hybrid exchange-correlation functional (B3LYP) and non-hybrid method (BLYP). Calculations were performed in vacuum and in methanol to study the effect of cis-trans geometry on the structure and energy difference between low-spin (LS) and high-spin (HS) states of iron (II) complexes. Full geometry optimizations of the complexes show that hybrid method consistently gives higher energy difference between LS and HS states than the nonhybrid methods. Calculations with reparameterized density functional theory that showed more reasonable electronic energy splittings in previous research was also carried out. In addition, the computational study of Fe(en)2(NCS)2 in vacuum and methanol with PCM method showed that the complexes tend to adopt cis geometry. This geometry showed much less charge transfer in the substitutions of NCS- ligands compare to trans geometry.